Comparative studies of iterative methods for solving the "optimally diffusive" coarse mesh finite difference accelerated transport equation. (July 2021) - Jain, Lakshay; Karthikeyan, Ramamoorthy; Kannan, Umasankari
Highlights: Comparison of different linear solvers for odCMFD accelerated neutron transport. Effect of coarse mesh size on performance of the schemes has been investigated. Effect of low-order convergence criteria on convergence behavior of these methods has been tested. Use of low order convergence criteria stricter than the high order has been recommended. Speed up of 195 and 26 times obtained for LRA-BWR and C5G7 problems, respectively. Abstract: The emergence of advanced nuclear reactor systems with increasing complexity and heterogeneity has necessitated detailed high fidelity neutronic analysis. This requires exhaustive solution of the neutron transport equation which has the disadvantage of long computation times, especially for scattering dominant problems. In this paper, the performance behavior and stability analysis of several iterative methods for solving the optimally diffusive coarse mesh finite difference (odCMFD) accelerated transport equation has been presented. Efficacy of the acceleration iterations with varying coarse mesh size and convergence criteria of the low order problem, and their overall performance has been investigated for the 2-group LRA-BWR problem and the 7-group C5G7 problem. Prescriptions for different parameters and the most robust iterative scheme have been proposed based on these studies. The theoretical background of odCMFD based acceleration schemes and the numerical results of their application to different problems using the code DIAMOND have been presented in this paper.